Custodians of Information: Patient and Physician Views on Sharing Medical Records in the Acute Care Setting. Issue 14 (6th December 2021) - Fritz, Zoe; Griffiths, Frances E.; Slowther, Anne-Marie
ABSTRACT: In the UK, in the acute in-patient setting, the only information that a patient receives about their medical care is verbal; there is no routine patient access to any part of the medical record. It has been suggested that this should change, so that patients can have real-time access to their notes, but no one has previously explored patient or clinician views on the impact this might have. Semi-structured interviews were conducted with 12 patients and 13 doctors about their experience of information sharing in the context of the acute care setting, and their views on sharing all of the medical records, or a summary note. Interviews were transcribed verbatim, double coded and analyzed using the constant comparative method. Patients were not given written information and did not ask questions even when they wanted to know things. Patients and doctors supported increased sharing of written information, but the purpose of the medical record – and the risks and benefits of sharing it – were disputed. Concerns included disclosing uncertainty, changing what was written, and causing patient anxiety. Benefits included increased transparency. Use of a summary record was welcomed as a way to empower patients, while doctors felt they had a responsibility to curate what information was given and when. A clinical summary for patients would be of benefit to doctors, nurses, patients and their relatives. It should be designed to reflect the needs of all users, and evaluated to consider patient-relevant outcomes and resource implications.